Eyelid edema as a rare manifestation of infectious mononucleosis - Marcinkowska, Adrianna; Cisiecki, Sławomir; Bonińska, Karolina; Bednarski, Maciej (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
We report the case of a 44-year-old woman presenting with edema of the upper eyelids and enlarged salivary glands. Slit lamp examination found features of bilateral dacryoadenitis with no abnormalities in the anterior and posterior segments. Based on the clinical manifestations and additional test results, the diagnosis of infectious mononucleosis was confirmed.